Basic Education Services for Schools and Community Learning Centers of the Division of Calamba City - Martir, Ligaya (JPAIR Institutional Research, 2019)
The Department of Education aims that all learners are given opportunities to be well-rounded by having access to programs responsive to their needs. However, reports show that problems on access and quality of learning still prevail, as evidenced by the number of students retained. This study looked into the factors that contribute to the increasing number of retained learners and the common problems encountered by the school heads in dealing with them. The study employed a descriptive design of research. A survey questionnaire, supplemented by informal interviews and a focus group discussion with 48 school heads and 314 teachers of selected schools and ALS mobile teachers of the Division of Calamba City, were utilized. Results revealed that the learners’ habitual tardiness and absences, and the lack of parental care and guidance in doing homework and other school projects, are the primary factors that contribute to the increasing number of retained learners. Moreover, the parents’ poor attendance during meetings and forums, and their attitudes in motivating their children to attend classes are the problems most often encountered by school heads. After a thorough analysis of data, a basic education services plan for schools and community learning centers in the Division of Calamba City was crafted to address the increasing number of retained learners.